Academic Senate Agenda 2006-11-30 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 10/26/06 approved. Computer Science Revision approved. Update on WASC. Statewide Senator report. Capping the Size of the Senate proposal failed. Sabbatical Policy revision first reading completed. Endorsement of Statewide Senate Resolution on Cornerstones first reading completed. Endorsement of Statewide Senate Resolution on ACR73 first reading completed. Cost Sharing policy referred back to FSAC with specific instructions.